Cardiac Electrophysiology Clinical Case Review - Natale, Andrea; Al-Ahmad, Amin.; Wang, Paul J.; DiMarco, John.; SpringerLink (Online service) (London : Springer London, 2011)
As the field of cardiac electrophysiology evolves, the challenge remains to educate new generations of cardiac electrophysiologists with the basics as well as the latest advances in the field. While there are many outstanding resources providing in-depth review of electrophysiology topics, there are few case-based books that comprehensively cover clinical electrophysiology, devices and ablation. Case review offers a simple, yet effective way in teaching important concepts, offering insight into both the basic pathophysiology of a problem as well as the clinical reasoning that leads to a solution. Cardiac Electrophysiology: Clinical Case Review collates the most comprehensive case-based reviews of electrophysiology designed to appeal to all students of the field whether they are fellows, allied professionals or practicing electrophysiologists. The Editors have recruited some of the true experts in the field to contribute cases that they have encountered and summarizing the important learning objectives in a succinct way. Covering clinical electrophysiology, device troubleshooting and analysis as well as intracardiac electrogram analysis and ablation, readers will find the cases useful as a review of electrophysiology or in their day to day interactions with patients.
Introduction.-Section 1: Ablation: Supraventricular Arrhythmias -- Atrial fibrillation -- Atrial Flutter -- Ventricular Arrhythmias.-Section 2: Devices: Pacemakers -- Implantable Cardioverter Defibrillators -- Biventricular devices.-Section 3: Clinical cases: Syncope -- Athletes and arrhythmias -- Ventricular arrhythmias -- Atrial fibrillation & atrial aflutter -- Supraventricular arrhythmias -- Arrhythmias associated with genetic abnormalities -- Hypertrophic cardiomyopathy.
Keywords: Medicine; Internal medicine; Cardiology; Heart -- Surgery; Medicine & Public Health; Cardiology; Internal Medicine; Cardiac Surgery